Community organization feedback about an undergraduate medical education service learning program - Berrington, Roger; Condo, Nina; Rubayita, Felicien; Cook, Karen; Jalloh, Chelsea (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Background: In 2016, Service Learning (SL) became a curricular requirement for undergraduate medical education (UGME) students at the University of Manitoba. Students partner with a community-based organization for two years to engage in non-clinical activities in community settings. Significant feedback has been collected from students re: their SL experiences. This project specifically collected feedback from community organizations involved with SL.Methods: In June 2019, an electronic survey was distributed to the 36 community organizations involved with SL.Results: Twenty-seven organizations completed the survey. Feedback was grouped into two main themes: 1) Logistics and 2) The SL Experience. About half (52%) of respondents indicated it was “easy” to schedule students for SL; however, students’ busy schedules and differences between hours of organization programming and students’ availability were highlighted. Most respondents described students as “engaged” (70%); respondents indicated SL raised students’ understanding of power and privilege (56%) and systemic oppression (63%).Conclusions: Community organizations shared valuable insights to inform the SL program. Results identified specific aspects of the SL program to address moving forward, such as sharing learning objectives with community partners. Ensuring processes are in place to obtain feedback from community partners is an essential step to improve SL programs, and to strengthen reciprocal community-university partnerships.